Integrated Thin Film Battery Design for Flexible Lithium Ion Storage: Optimizing the Compatibility of the Current Collector‐Free Electrodes. (25th August 2019) - Zhao, Wenyu; Bai, Miao; Li, Shaowen; Tang, Xiaoyu; Wu, Weiwei; Sun, Changchun; Yin, Xiaokang; Zhou, Jie; Yuan, Shuai; Ma, Yue
Abstract: The design of flexible full‐cell configuration relies on the light‐weight arrangement, structural robustness, compositional compatibility, and shape conformability of the coherent components. In this article, a general and scalable spin‐coating approach is developed to integrate the flexible, current‐collector‐free cathode and anode in the thin film batteries with the layer‐stacked configuration. The design of the ternary composite anode involves the reduced graphene oxide encapsulation of the MoS2 /N‐doped carbon microrods composite (rGO‐MoS2 /NC) via the facile hydrothermal‐calcination process. In the similar structure design of the cathode, the ball‐milled nanocrystalline mixture of LiMn2 O4 and LiVPO4 F is wrapped within the GO interfacial protection layer. Furthermore, the slurries of electroactive materials with the predetermined areal capacity ratio of negative to positive electrodes (N/P ratio) are cast onto both sides of the nano‐SiO2 modified polyethylene (SiO2 ‐MPE) separator via the facile spin‐coating process. The prototype full‐cell configuration delivers a high reversible capacity, satisfactory capacity retention at the high rate, as well as good cyclability under different mechanical loadings. This integrated thin film battery model showcases its potential use in the flexible electronic devices. Abstract : A structural robust, mechanical flexible full‐battery prototype is constructed by integrating the ternary composite anode (rGO‐MoS2 /NC‐30) and the nanocrystalline composite cathode (20%GO‐LVPF/LMO) cast on both sides of a nano‐SiO2 modified polyethylene (SiO2 ‐MPE) separator via spin‐coating procedures.